SUPERVISION OF THE PEOPLE'S REPRESENTATIVE COUNCIL OVER THE PRESIDENT'S POLICY IN DECLARING A STATE OF EMERGENCY: PENGAWASAN DEWAN PERWAKILAN RAKYAT TERHADAP KEBIJAKAN PRESIDEN DALAM PENETAPAN STATUS DARURAT NEGARA - Kaleb Anggi Three Putra Sagala; Haposan Siallagan; Januari Sihotang (Pusat Studi Konstitusi dan Perundang-undangan, 2026)
This research is motivated by the increasing use of emergency powers by the President in responding to national crises which has the potential to expand executive power and impact the protection of citizens' rights. This research aims to analyze the regulation and effectiveness of the DPR RI's supervision of the President's policy in determining state emergency status based on Article 12 of the 1945 Constitution of the Republic of Indonesia. The method used is normative juridical research with a qualitative descriptive analytical approach through literature study and analysis of statutory regulations. The research results show that normatively the DPR RI's oversight mechanism has been regulated through legislative, budget and oversight functions, including approval of Government Regulations in Lieu of Laws. However, empirically, this supervision still tends to be formal and does not fully guarantee accountability and protection of citizens' rights. Therefore, the DPR RI's supervisory function needs to be strengthened so that the principles of the supremacy of law and constitutional democracy are maintained in emergency conditions.